Assessment of environmental controls on acid‐sulfate alteration at active volcanoes in Nicaragua: Applications to relic hydrothermal systems on Mars. Issue 10 (7th October 2013) - Hynek, Brian M.; McCollom, Thomas M.; Marcucci, Emma C.; Brugman, Kara; Rogers, Karyn L.
<x xml:space="preserve">Abstract</x> [1] A variety of secondary mineralogies has been detected on Mars from both orbiters and landers, indicating widespread aqueous alteration of the crust. Many of these locales exhibit sulfates, which in some cases imply acidic fluids. At present, there are few constraints on the paleoenvironmental conditions that existed during formation of the widespread and diverse classes of secondary minerals on Mars. We investigated hydrothermal systems at three active acidic volcanic systems in Nicaragua, including Cerro Negro, Momotombo, and Telica. The recently erupted materials are similar in composition to the Martian crust and are undergoing extensive acid‐sulfate alteration predominately in gas‐dominated settings (fumaroles). We characterized the secondary mineralogy and local variables, including temperature, pH, rock and gas composition, and fluid‐rock ratio. We find that these environmental parameters exhibit strong controls on the alteration mineralogy. The environments studied include pH that ranged from −1 to 6, temperatures from ambient to hundreds of degrees Celsius, and fumaroles to hot springs. The hottest and most acidic systems contained sulfur, silica, and minor gypsum, while moderately acidic and cooler fumaroles included abundant silica, gypsum and other hydrated sulfates, and phyllosilicates. A setting with a higher fluid‐rock ratio but similar temperature and acidity was dominated by phyllosilicates and, to a lesser degree, sulfates. The characterization of aqueous alteration of basalts under a variety of environmental conditions provides a conceptual framework for interpretation of similar relic environments on Mars. Finally, while identification of phyllosilicates on Mars is generally thought to require neutral to alkaline fluids, we documented significant formation of these minerals in the acidic volcanic systems.